2021
DOI: 10.1177/0271678x211019827
|View full text |Cite
|
Sign up to set email alerts
|

Functional dynamics of dopamine synthesis during monetary reward and punishment processing

Abstract: The assessment of dopamine release with the PET competition model is thoroughly validated but entails disadvantages for the investigation of cognitive processes. We introduce a novel approach incorporating 6-[18F]FDOPA uptake as index of the dynamic regulation of dopamine synthesis enzymes by neuronal firing. The feasibility of this approach is demonstrated by assessing widely described sex differences in dopamine neurotransmission. Reward processing was behaviorally investigated in 36 healthy participants, of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 71 publications
2
29
1
Order By: Relevance
“…Female mice showed less brain damage than male mice following global cerebral ischemia, and the incidence of vascular events was lower in female stroke‐prone hypertensive rats than that in males after focal cerebral ischemia 69,70 . Sex dimorphism also exists in dopamine neurotransmission, resulting in males being more sensitive to reward and females to punishment 71 . Moreover, sex influences both brain microvessels and functional improvement after cerebral ischemia 72,73 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female mice showed less brain damage than male mice following global cerebral ischemia, and the incidence of vascular events was lower in female stroke‐prone hypertensive rats than that in males after focal cerebral ischemia 69,70 . Sex dimorphism also exists in dopamine neurotransmission, resulting in males being more sensitive to reward and females to punishment 71 . Moreover, sex influences both brain microvessels and functional improvement after cerebral ischemia 72,73 .…”
Section: Discussionmentioning
confidence: 99%
“… 69 , 70 Sex dimorphism also exists in dopamine neurotransmission, resulting in males being more sensitive to reward and females to punishment. 71 Moreover, sex influences both brain microvessels and functional improvement after cerebral ischemia. 72 , 73 However, our experiments were carried out in both male and female rats at an equal ratio of 1:1, and we did not explore the impact of sex differences in HIBI‐related long‐term learning and memory abilities.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study measured cerebral 5‐HT 1B R binding in a group of PD patients with STN‐DBS, and found that they exhibited a significant loss of frontal and parietal 5‐HT 1B R, which indicated STN‐DBS dynamically regulated the serotonin system in PD, 37 but whether this regulation was affected by age and disease duration still needs to be investigated. Hahn et al found monetary gain‐induced stronger increases in ventral striatum dopamine synthesis than that of the loss in young men; however, the opposite effect was discovered in young women, indicating a neurobiological basis for known behavioral sex differences in reward and punishment processing 38 . Chandra et al revealed major sex disparities (young male and female rats) in gene expression and canonical pathways of microvessels and these differences provided a foundation to study neurological diseases 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Hahn et al found monetary gain‐induced stronger increases in ventral striatum dopamine synthesis than that of the loss in young men; however, the opposite effect was discovered in young women, indicating a neurobiological basis for known behavioral sex differences in reward and punishment processing. 38 Chandra et al revealed major sex disparities (young male and female rats) in gene expression and canonical pathways of microvessels and these differences provided a foundation to study neurological diseases. 39 Meanwhile, a previous study showed that young women had significantly higher cerebral blood flow than men in the frontal and temporal lobes, but these differences disappeared at age 65 years.…”
Section: Discussionmentioning
confidence: 99%
“…In waiting for such radioligands, existing radioligands have been put to creative use. Hahn and co-workers used [ 18 F]DOPA and a constant infusion design, where task-related deviation from expected linear increase in tracer uptake was calculated to study the dopaminergic underpinnings of reward processing, thereby making the temporal resolution of neurotransmitter release more equal to the level of fMRI [ 77 ]. For tracers with reversible kinetics, steady-state methods using bolus-infusion protocols can be used to measure changes in binding after a pharmacological challenge.…”
Section: Introductionmentioning
confidence: 99%